Can the ratio of metastatic to examined lymph nodes (N ratio) be used as an independent prognostic factor in patients with gastric cancer? Is the hypothetical TRM (tumor-ratio-metastasis) staging system an alternative to the TNM (tumor-node-metastasis) staging system? - Ilhan, Enver; Zengel, Baha; Simsek, Hatice; Canpolat, Selin; Yildirim, Mehmet (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Aim: Lymph node metastasis is the most important prognostic factor in patients with gastric cancer. However, lymph node classification is controversial. We reported the prognostic factors of gastric cancer and the impact of N ratio classification in predicting prognosis and the suitability of TRM classification as an alternative to TNM(tumor-node-metastasis) classification for lymph nodes to avoid stage migration in gastric cancer. Material and methods : A total of 90 patients, who underwent R0 resection for gastric cancer, were analyzed. Independent variables of the study were age, gender, tumor site, type of surgery, lymph node dissection, tumor size, T stage, differentiation, total number of removed lymph nodes, number of metastatic lymph nodes, N ratio, N stage, and TNM stage. N ratio was used instead of N stage in the hypothetical TRM staging system. Dependent variables of the study were 2-year and 5-year survival rates. Results: The N ratio cutoff points were 0, 0.10, and 0.25. The 2-year and 5-year survival rates were significantly higher in patients who had low T stages (p < 0.001, p < 0.001), N stages (p < 0.001, p < 0.001), N ratio (p < 0.001, p < 0.001), TNM stages (p < 0.001, p < 0.001), and underwent subtotal gastrectomy (p = 0.006, p = 0.030). When the TNM stages of the patients according to the UICC/AJCC TNM sixth and seventh edition staging system were compared to theTRM hypothetical staging system, stage migration phenomenon was observed at 36.6% and 8.8%, respectively. Conclusions : N ratio classification can be used as an independent prognostic factor. The use of TRM hypothetical staging system for minimizing stage migration phenomenon requires further discussion.